PENGGUNAAN BENCHMARKING DALAM UTILITAS AIR MINUM - Winarni , (Media Riset Bisnis & Manajemen, 2007)
Benchmarking is the process of improving performance by continuously identifying, understanding, and adapting outstanding practices and processes found inside and outside the organization. Many companies and large organizations have embraced benchmarking as an important, systematic methodology for achieving the organization's strategic objectives. Benchmarking focuses on how to improve any given business process by exploiting best practices rather than merely measuring the best performance. Studying best practices provide the greatest opportunity for gaining a strategic, operational, and financial advantage. The Benchmarking System, named BMS2, was established by Indonesian Association Water Companies (PERPAMSI) during 2003 when 79 PDAMs contributed data to provide 29 indicators. The two key objectives of BMS2 are to understand the ability to achieve and maintain cost recovery and the community satisfaction with the service provided by their PDAM.Keywords : Benchmarking, Best Practice, Key Performance Indicators (KPI)